(untitled) (Research, Society and Development, 2021)
Introduction: Maximum oxygen consumption (VO2max) is the variable that is related to cardiorespiratory fitness and represents the body’s maximum capacity to capture, transport and use oxygen by cells during physical exercise. Objective: This study aimed to determine the VO2max through the indirect test, in university students practicing sports activities of different modalities. Methodology: characterized as descriptive, prospective, transversal comparative. The sample consisted of 14 students practicing different sports at the Centro Universitário Santo Agostinho in the city of Teresina, Pi. Data collection was performed behind the 2400 meter run test on the Parque Potycabana running track. Results: 14 volunteers who met the inclusion criteria of the study 10 were male (71.4%) and 4 female (28.6%), 8 futsal volunteers (57.1%) and 6 handball (42.9%). The Chi-square association test of association of social qualitative data (age, sex and sport modality) was used, the mean comparison test was also used for quantitative data for physiological results (training frequency, initial mean blood pressure , final mean arterial pressure, heart rate, respiratory rate, saturation, VO2). Conclusion: The study proved that there is a significance level between VO2 max, physical fitness, gender, final average heart rate and time of travel, present in the 14 athletes evaluated. No significant results were found between the variables: modality, compared to the level of VO2 max and age.